Improving the Mechanism of Using Modern Technologies in Teaching English Language to Primary Education Students - Akobirova Kamola Malikovna; Yakubova Kamola Shokirovna (Open Academia, 2023)
In this article, the improvement of the mechanism of using modern technologies in teaching English to elementary school students, the age, physiological, and psychological characteristics of the student in teaching foreign languages to students in primary grades, especially in the first grade. should be taken into account, it is reported that sound cards with multimedia technologies allow users to record their own speech and then compare it with the speakers' pronunciation.
Keywords: Multimedia; interactive; innovative